Boba kefir pineapple beverage innovation: Probiotic and antioxidant refreshment - Devi Nur Na'syifa Komar; Judiono Judiono (AcTion: Aceh Nutrition Journal, 2025)
Nutritional intake plays an important role in boosting the immunity. This study aimed to modify the boba drink into a probiotic- and antioxidant-rich drink. Kefir is a source of probiotics. Pineapples, which are rich in vitamin C, have antioxidant properties. The experimental study used a completely randomized design (CRD) with three formulations: F1 (75% kefir: 25% pineapple), F2 (50% kefir: 50% pineapple), and F3 (25% kefir: 75% pineapple). Product manufacturing and organoleptic tests were conducted at the Food Laboratory of Poltekkes Kemenkes Bandung. Laboratory testing was conducted at Saraswanti Indo Genetech and Sibaweh Lab. This research was conducted from December 2022 to January 2023. Organoleptic testing was performed by 30 trained panelists. Analysis using the Kruskal–Wallis test. Results: There were differences in the organoleptic aspects (p= 0,012) of each formulation. Thus, F3 was found to be the best formulation. The number of lactic acid bacteria was 6,7 x 106, with antioxidant activity of 1238,02 ppm or 0,1238%, and vitamin C content of 19,88 grams. In conclusion, the high antioxidant activity of this drink suggests that it has the potential to increase body immunity. Further testing is needed to determine the type and number of other probiotic bacteria present in the product.